Tempe “Mendol” as Traditional Side Dish for Rural Gastronomy Tourism in Malang, East Java. - Sandy Dwiputra Yubianto (INSPIRE : Journal of Culinary, Hospitality, Digital & Creative Arts and Event, 2024)
Indonesia is well known for its manmade food creation called tempe. People fell in love with the crispy and tanginess that tempe produced due to its fermentation process of the raw ingredients which is soybean. This product is highly varied upon its forms and processing techniques. One of the most famous menu is mendol. Mendol is created by letting Tempe pass beyond the ripping stage and passing the peak of its quality to go almost starting to rotten slowly. This unique dishes has made most of the local people able to process a product that way passed its expiry date and still edible. This study focused on examining the potential of mendol to become the iconic and unique product for Gastronomy in East Java. The study uses literature review to see the potential in exposing mendol for Gastronomy Tourism and to seek the possible market for this kind of tourism. the research resulted in the possibility of bringing back Mendol as part of the commercial dishes in gastronomy tourism seems to be applicable. This also helps the destination in retaining as well as gaining new visitor via the marketing of local food and mendol is one of the traditional food that has its own unique story for East Java especially Malang area.